Absence of Regulatory T Cells Causes Phenotypic and Functional Switch in Murine Peritoneal Macrophages - Skuljec, Jelena; Jirmo, Adan Chari; Habener, Anika; Talbot, Steven R.; Pul, Refik; Grychtol, Ruth; Aydin, Malik; Kleinschnitz, Christoph; Happle, Christine; Hansen, Gesine (Frontiers in Immunology, 2018)
Tissue macrophages are important components of tissue homeostasis and inflammatory pathologies. In the peritoneal cavity, resident macrophages interact with a variety of immune cells and can exhibit broad range of phenotypes and functions. Forkhead-box-P3 (FOXP3)+ regulatory T cells (Tregs) play an indispensable role in maintaining immunological tolerance, yet whether, and how the pathological condition that results from the lack of functional Tregs affects peritoneal macrophages (PM) is largely unknown. We used FOXP3-deficient scurfy (Sf) mice to investigate PM behavior in terms of the missing crosstalk with Tregs. Here, we report that Treg deficiency induced a marked increase in PM numbers, which was reversed after adoptive transfer of CD4+ T cells or neutralization of macrophage colony-stimulating factor. Ex vivo assays demonstrated a pro-inflammatory state of PM from Sf mice and signs of excessive activation and exhaustion. In-depth immunophenotyping of Sf PM using single-cell chipcytometry and transcriptome analysis revealed upregulation of molecules involved in the initiation of innate and adaptive immune responses. Moreover, upon transfer to non-inflammatory environment or after injection of CD4+ T cells, PM from Sf mice reprogramed their functional phenotype, indicating remarkable plasticity. Interestingly, frequencies, and immune polarization of large and small PM subsets were dramatically changed in the FOXP3-deficient mice, suggesting distinct origin and specialized function of these subsets in inflammatory conditions. Our findings demonstrate the significant impact of Tregs in shaping PM identity and dynamics. A better understanding of PM function in the Sf mouse model may have clinical implication for the treatment of immunodysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome, and other forms of immune-mediated enteropathies.